11-Keto-testosterone and other androgens of adrenal origin - Stárka, L; Dušková, M; Vítků, J (Physiological research, 2020)
The adrenal glands produce significant amounts of steroid hormones and their metabolites, with various levels of androgenic activities. Until recently, the androgenic potency of these adrenal-derived compounds were not well known, but some recent studies have shown that the production of 11-oxo- and 11beta-hydroxy-derived testosterone and dihydrotestosterone evidently have high androgenic activity. This fact has clinical importance, for instance, in various types of congenital adrenal hyperplasia with androgenization or polycystic ovarian syndrome, and laboratory determinations of these substances could help to better evaluate the total androgen pressure in patients with these disorders. Another area of concern is the treatment of prostate cancer with androgen deprivation, which loses effectiveness after a certain time. The concurrent blocking of the secretion of adrenal C(19)-steroids, whether using corticoids or adrenostatics, could increase the effectiveness of androgen-deprivation therapy.
Keywords: Androgens; Molecular Targeted Therapy; Prostatic Neoplasms; nádory prostaty; Androgen Antagonists; Animals; Humans; mužské pohlaví; androgeny; lidé; antagonisté androgenů; testosteron; zvířata; kongenitální adrenální hyperplazie; Adrenal Hyperplasia, Congenital; Male; Testosterone; cílená molekulární terapie